Transforming Classrooms through PBL: Lessons from Indonesia’s Curriculum Reforms and Global South Contexts - M, Usman (Indonesian Scientific Publication, 2025)
Project-Based Learning (PBL) has been recognized as a transformative educational model for enhancing 21st-century competencies, particularly in developing countries undergoing curricular reforms. In Indonesia, the Merdeka Curriculum and its P5 framework have adopted PBL as a central pedagogical strategy. This study evaluates the outcomes and implementation fidelity of Project-Based Learning (PBL) in Indonesian secondary schools through synthesis of global and local empirical evidence. Using a meta-synthesis approach, the study integrates quantitative and qualitative data from peer-reviewed research, quasi-experimental designs, and policy evaluations. Validated tools such as the California Critical Thinking Skills Test (CCTST) and Tibi’s Collaboration Questionnaire were used to assess student outcomes. Fidelity of implementation was analyzed through project duration, professional development (PD), and adherence to Gold Standard PBL criteria. Findings reveal moderate-to-large effect sizes of PBL on student critical thinking (SMD = 0.82 in high schools) and collaboration (SMD = 0.94 in middle schools). Extended project duration (≥6 weeks), structured PD, and alignment with authentic PBL elements significantly enhance learning outcomes. However, institutional and cultural constraints such as rigid assessment systems and teacher-centered traditions undermine PBL fidelity in Indonesian classrooms. Comparative analysis with other Global South nations reveals similar challenges, highlighting the need for localized yet globally aligned implementation strategies. While PBL holds strong potential to transform student learning in Indonesia, its effectiveness depends on systemic supports, including targeted PD, curricular alignment, and culturally responsive assessment frameworks. This study offers a fidelity-sensitive roadmap for scaling PBL in developing contexts and contributes to the discourse on reforming instructional practices for future-ready education